Membangun Profesionalisme Pengurus Koperasi Melalui Digitalisasi Untuk Meningkatkan Pelayanan Kepada Anggota di Primer Koperasi Produsen Tempe Tahu (Primkopti) Sleman - Farida, dkk, Farida (LPPM Universitas Koperasi Indonesia, 2024)
Praktik Lapang (field practice) activities at the Primary Cooperative of Tempeh and Tofu Producers (Primkopti) Sleman aim to deepen students' understanding of the cooperative's identity concept and its implementation in the management of the cooperative organization and its business activities. The field practice results identified four problems: ineffective and inaccurate manual financial report recording, unsystematic meeting documentation, a non-compliant organizational structure with legal regulations, and the management's lack of knowledge about members' satisfaction with cooperative services. Based on the problems, the writers conducted some activities 1) the development of an Excel-based computerized accounting system, 2) the digital recording of cooperative management meetings for efficient decision-making, 3) the arrangement and printing of an organizational structure banner, and 4) the development of a customer satisfaction questionnaire to improve service quality and member satisfaction.